The gendering of entrepreneurship context - Friederike Welter; Candida Brush; Anne De Bruin (Institut für Mittelstandsforschung (IfM) Bonn, 2014)
The paper builds on the understanding of context as suggested by Welter (2011) who introduced different dimensions of context along a continuum of where entrepreneurship takes place and when this happens. Where context has been studied in relation to gender and women, the focus has been on the influence of social contexts such as networks, family and household embeddedness of women entrepreneurs or the institutional environment for women's entrepreneurship. We contribute to the literature by identifying three further themes, based on a systematic literature review: how to conceptualise the spatial and institutional contexts for women's entrepreneurship and their intersections, as informed by entrepreneurship, gender and geography studies; the paradox of empowering women and the debate around mumpreneurship. Our analysis highlights the influence of spatial-institutional contexts on entrepreneurship: Entrepreneurial behaviour is gendered because of place which itself is gendered, reflecting local institutions such as accepted gender norms which may force women into specific industries or business sizes. We also highlight the agency of women entrepreneurs in influencing their spatial-institutional contexts.
Keywords: J16; L26; M13; 330; entrepreneurship; women's entrepreneurship; gender; entrepreneurship context